Analisis Faktor-Faktor Yang Mempengaruhi Underpricing Ketika Initial Public Offering (Ipo) Di Bursa Efek Indonesia (Bei) Tahun 2008-2012 - Muktia Apriliani, Kukuh; , Drs. Agus Endro S, M.Si (2015)
Underpricing is phenomenon when opening stock price of the company made its first offer in the primary market is lower than closing stock price in the secondary market. Stock price at the time of the initial public offering is determined by the issuer (company) and underwriters. However, the stock price in the secondary market mechanism occurs is determined by supply and demand result. The companies that doing initial offering avoid underpricing, because the company did not get the maximum funds from the sale of shares of its inaugural. The company that doing IPO at Indonesia Stock Exchange on 2008-2012 period are 106 company and the underpricing happened on 56 company or about (52,83%). So that this research aims to analyze the determinant factors of underpricing. Independent variables of the research are firm zise, ROE, DER, and underwriter reputation. The population of this research are, all the company in Indonesia Stock Exchange that doing IPO in the 2008-2012 period. Sample is collected by using purposive sampling, so that the sample used in this study were 39 companies. Secundary data sources obtained from the Indonesian Capital Market Directory (ICMD), www.idx.co.id, and www.e-bursa.com. Data analysis is performed by multiple linear regression analysis. Regression analysis shows that only underwriter reputation has a significant effect on underpricing. Meanwhile, firm size ROE and DER has no effect on underpricing. This result had implication that companies doing IPO should consider underwriter to attracct investors and minimize the level of underpricing